Evaluation of Minimization and Storage Management of Medical Waste at Hospital During the Covid-19 Pandemic - Aura Dhia Rizki Atthar; Mega Mutiara Sari; Iva Yenis Septiariva; I Wayan Koko Suryawan (Politeknik Sukabumi, 2022)
Health facilities such as hospitals produce medical waste and non-medical waste. Improper management of medical waste can cause the spread of infectious nature, especially during the Covid-19 pandemic. Therefore, management at the source, such as minimization and containment, is important and must be evaluated. This study evaluates hospital medical waste management based on minimization and containment efforts. This research was conducted by direct observation and literature review. The findings on minimization efforts are following regulations such as reducing the use of materials containing hazardous and toxic materials if there is a choice, avoiding accumulation and expiration of the procurement of chemicals and pharmaceuticals, and separating non-medical and medical waste according to the waste category. The container also meets the standard where the container is equipped with a cover and is made of puncture-resistant material. The containers are also equipped with bags and symbols according to the characteristics of the waste with internal transportation at least once a day or when the container has been filled. Garbage officers prepare medical waste handover documents. Transportation from the production source to the temporary shelter (TPS) uses a yellow trolley with a biohazard symbol, tightly closed with a predetermined route, and cleaning and disinfection are carried out on the trolleys that are used every day.